2009
DOI: 10.1128/aem.00398-09
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genome-Wide Transcriptional Profiling of Azorhizobium caulinodans ORS571 Grown under Free-Living and Symbiotic Conditions

Abstract: The whole-genome sequence of the endosymbiotic bacterium Azorhizobium caulinodans ORS571, which forms nitrogen-fixing nodules on the stems and roots of Sesbania rostrata, was recently determined. The sizes of the genome and symbiosis island are 5.4 Mb and 86.7 kb, respectively, and these sizes are the smallest among the sequenced rhizobia. In the present study, a whole-genome microarray of A. caulinodans was constructed, and transcriptomic analyses were performed on free-living cells grown in rich and minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 77 publications
2
32
0
Order By: Relevance
“…The labeled cDNA was mixed with 3.3 l of control oligo(B2) (3 nM; Affymetrix) and 100 l of 2ϫ hybridization mix (Affymetrix) in a volume of 200 l and used in the subsequent hybridization. Hybridization, washing, staining, and scanning were performed as previously described (48). To evaluate the differentially expressed genes, the weighted average difference (WAD) method (25,26) was applied to the log 2 signal.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The labeled cDNA was mixed with 3.3 l of control oligo(B2) (3 nM; Affymetrix) and 100 l of 2ϫ hybridization mix (Affymetrix) in a volume of 200 l and used in the subsequent hybridization. Hybridization, washing, staining, and scanning were performed as previously described (48). To evaluate the differentially expressed genes, the weighted average difference (WAD) method (25,26) was applied to the log 2 signal.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we constructed a whole-genome microarray of A. caulinodans and performed transcriptional profiling experiments with A. caulinodans in the free-living and symbiotic states (48). By the screening of Tn5 mutants, we identified 86 genes that were required for A. caulinodans to establish symbiosis (43).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, no putative TBDRs for thiamine or phytate were identified. This is reasonable because phytate is not a source of phosphorus in the habitats of rhizobacteria (26), and rhizobacteria have the ability to synthesize thiamine (28,36,49). The heme-specific and siderophore-specific TBDRs in rhizobacteria are likely to be responsible for the uptake of heme and iron under free-living conditions, rather than during symbiosis, as their expression is downregulated in bacteroids.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…In a previous study, we identified many genes that are involved in the developmental process of nodulation through a large-scale in vivo screening of Tn5-inserted mutants of A. caulinodans ORS571 (68). In addition, the genome-wide transcriptional profiles of A. caulinodans ORS571 in free-living and symbiotic states have been established by microarray analyses (71).…”
mentioning
confidence: 99%